(untitled) (International Seven Journal of Multidisciplinary, 2023)
The Covid-19 pandemic has challenged health professionals working on the front lines of this serious health situation, especially the ability to perform the mechanical ventilation technique on patients who need respiratory support. The handling and technique of a mechanical ventilator is one of the biggest concerns of these professionals in hospital, emergency and urgency health services. And improvement can occur through theoretical-practical training, in person or remotely. Thus, this study aims to evaluate the efficiency of face-to-face and remote teaching of mechanical ventilation for health professionals. To achieve our objective, an Educational Product (EP) was developed in the form of a website, questionnaires and video classes with theoretical content and practical demonstrations of the technique. Through the present research, a gap in pre-existing knowledge was observed in some professionals who already worked directly with the subject before training. After remote teaching, a significant number of participating health professionals correctly answered the post-test questions. It is suggested that this small deficiency in knowledge about MV can be carried out with training with newly trained professionals who will go to the job market. Although remote teaching participants showed lower performance in the post-test when compared to the pre-test, this group got more questions right than professionals who received the training in person.